The Holistic Education Concept According to KH Imam Zarkasyi - Asroriah, Fatimatul; Hanafi, Yusron; Machmud Putra, Errizal (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
Holistic education has become a primary focus in the world of education, with an emphasis on comprehensive personal development. One of the education figures who has implemented this concept effectively is KH Imam Zarkasyi, a prominent leader of Islamic boarding schools in Indonesia. This research aims to explore the holistic education concept applied by KH Imam Zarkasyi and its implications in the context of modern education. The research method used is literature review and content analysis of primary and secondary sources related to Imam Zarkasyi's holistic education concept. From the analysis, it is found that KH Imam Zarkasyi's holistic education concept encompasses a comprehensive approach that integrates academic, spiritual, social, and physical aspects in education. This approach also emphasizes integrated learning inside and outside the classroom, balanced personal development, the crucial role of Kiai as leaders and role models, and the involvement of parents and communities in supporting holistic education. The conclusion of this research is that KH Imam Zarkasyi's holistic education concept has high relevance in the context of modern education, as it focuses on comprehensive personal development and the integration of various aspects of life in the educational process. The practical implication is the need for a more holistic and effective educational approach in creating a learning environment that stimulates comprehensive development for students. Thus, KH Imam Zarkasyi's holistic education concept can serve as inspiration and guidance for efforts to enhance the quality